Optimizing The Understanding Of The Values Of The Hikayat Text Through Interactive Media Quizizz: A Descriptive Qualitative Study at Al-Islamiyah High School - Moh Mahrus Shofi; Nor Afni Dian Maulidini; Wasilurrahman Wasilurrahman; Ulil Absor R.S.D; Shinta Widia Sari; Ainur Rofiq Hafsi (Molang: Journal Islamic Education, 2026)
The appreciation of classical literature, specifically hikayat texts, often faces a pedagogical impasse due to the dominance of conventional lecture methods, which induce student passivity, erode intrinsic motivation, and cause cognitive overload. This descriptive qualitative study aims to describe the operational process and impact of integrating Quizizz, a digital gamification platform, with a Discovery Learning framework and visual scaffolding to optimize comprehension of hikayat material. Conducted at SMA Al-Islamiyah, the study involved 30 tenth-grade students and an Indonesian language teacher. Data were gathered multi-dimensionally through semi-structured interviews, participant observation, Quizizz digital footprint extraction, and student perception questionnaires. The findings indicate that implementing Quizizz, initiated by cognitive stimulation via the "Rawa Pening" comic strip, significantly boosted enthusiasm and active participation, while creating a positive, competitive classroom atmosphere. Cognitively, the average class accuracy rate reached 70%, with the highest comprehension concentrated on social values (87%), despite lingering ambiguity in interpreting cultural values. Conclusively, these findings confirm that classical literature is no longer perceived as obsolete when contextualized through a hybrid approach that merges visual mediums, independent inquiry frameworks, and gamified evaluations highly resonant with the digital ecosystem of today's generation.